China's Free Trade Agreement Strategy: What lies beneath? - Leifur Sefton Sigurðsson 1985- (2014)
The objective of this thesis is to better understand the primary political and economic considerations motivating China’s relentless pursuit of free trade agreements (FTAs) since the early 2000s. It will examine the reasons behind China’s initial drive for FTAs as well as the on-going considerations motivating its overall FTA strategy and its selection of free trade partners. These considerations motivating China’s free trade will be grouped into geo-political, political/diplomatic, and economic considerations. A closer look will also be taken of China’s FTAs with its first two Western free trade partners, New Zealand and Iceland, in order to better understand the factors motivating China’s desire for closer economic integration with the West. Several international relations theories such as realism, mercantilism and liberalism will be utilized in order to assess how well they relate to China’s actions on the international free trade scene, bringing to light the theoretical principles underlining China’s free trade actions. The thesis will close with a description of the various political and economic considerations that have influenced China’s FTA strategy to date, and detail the importance of this knowledge in understanding China’s past, present and future free trade actions and intentions. The thesis concludes that China’s free trade behavior thus far has been one characterized by mostly open and liberal calculations, pointing to China’s overall cooperative international free trade conduct.